2017
DOI: 10.1016/j.ntt.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to anesthesia-induced neurotoxicity and its implications for future mechanistic studies

Abstract: The year 2016 marked the 15th anniversary since anesthesia-induced developmental neurotoxicity and its resulting cognitive dysfunction were first described. Since that time, multiple scientific studies have supported these original findings and investigated possible mechanisms behind anesthesia-induced neurotoxicity. This paper reviews the existing mechanistic literature on anesthesia-induced neurotoxicity in the context of a holistic approach that emphasizes the importance of both neuronal and non-neuronal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 127 publications
(158 reference statements)
0
20
0
Order By: Relevance
“…Regarding the side effects of anesthetics, it is clear that some off-target effects, for example cardiac arrhythmias and myocardial depression, stem from effects on non-neural ion channels (Zanghi & Jevtovic-Todorovic, 2017 disturbances in the development and maturation of the central nervous system may be owing to effects on glial cells as well as the effects of decreased synaptic activity on neurons (Zanghi & Jevtovic-Todorovic, 2017), some of which are potentially reversible through the application of receptor agonists (Huang et al, 2016). Regarding the most-feared issue of apoptosis in the developing brain (Ikonomidou et al, 2001;Zanghi & Jevtovic-Todorovic, 2017), the issue is less clear. Mitochondria are crucial components of the apoptotic pathway, releasing cytochrome c and other factors that direct the cell towards cell death (Boulbrima et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the side effects of anesthetics, it is clear that some off-target effects, for example cardiac arrhythmias and myocardial depression, stem from effects on non-neural ion channels (Zanghi & Jevtovic-Todorovic, 2017 disturbances in the development and maturation of the central nervous system may be owing to effects on glial cells as well as the effects of decreased synaptic activity on neurons (Zanghi & Jevtovic-Todorovic, 2017), some of which are potentially reversible through the application of receptor agonists (Huang et al, 2016). Regarding the most-feared issue of apoptosis in the developing brain (Ikonomidou et al, 2001;Zanghi & Jevtovic-Todorovic, 2017), the issue is less clear. Mitochondria are crucial components of the apoptotic pathway, releasing cytochrome c and other factors that direct the cell towards cell death (Boulbrima et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The milestones of neurobehavioral development vary across species but the developmental progression in general is comparable. In the first weeks of life, critical neurodevelopment occurs; apoptosis, synaptogenesis, gliogenesis, and myelination, regardless of biological differences between species …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GA were also found to induce various types of neurodegeneration, such as apoptosis of oligodendrocytes and neurons, microglial activation, cytoskeletal abnormalities of astrocytes, imbalanced differentiation of neural precursor cells, disruption of mitochondrial dynamics, and even damage to the blood-brain barrier. Because the neurodegenerative changes and potential injury mechanisms were thoroughly and elaborately outlined in recently published reviews [6][7][8]11], we will not repeat it in the present paper.…”
Section: Advance In Rodentsmentioning
confidence: 99%
“…Among this research, a landmark study in this field showed that PND7 rats exhibited neuroapoptosis in a variety of brain regions and prolonged impairment in learning and memory after exposed to a commonly used anesthetic cocktail (N 2 O-midazolam-isoflurane) for 6 h [5]. Subsequent preclinical studies demonstrated that GA caused a vast amount of acute injury and long-term cognitive impairments in rodents [6][7][8][9][10][11][12][13] and nonhuman primates (NHP) [9,10,[14][15][16][17][18][19][20][21][22][23]. Even worse, exposure to GA in neonatal rodents produced adverse effects on the learning and memory of their offspring via epigenetic modulation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%